A NEW APPROACH TO THE DEVELOPMENT AND RESEARCH OF THE IMPELLER CONFIGURATIONS IN TURBULENT MIXING OF THE MOLDING SANDS COMPONENTS - D. M. Kukuj; Ju. P. Ledjan; A. V. Stelmah (Литьë и металлургия, 2006)
The new approach to the development and investigations of the impellers configuration at turbulent stirring of the agglutinant sands is given